COPD Assessment Test for measurement of health status in patients with idiopathic pulmonary fibrosis: A cross‐sectional study. Issue 4 (9th November 2016) - Matsuda, Toshiaki; Taniguchi, Hiroyuki; Ando, Masahiko; Kondoh, Yasuhiro; Kimura, Tomoki; Kataoka, Kensuke; Sakamoto, Koji; Suzuki, Atsushi; Furukawa, Taiki; Hasegawa, Yoshinori
ABSTRACT: Background and objective: The COPD Assessment Test (CAT) has been reported to have potential utility for measuring health status of idiopathic pulmonary fibrosis (IPF). Although the CAT has been developed for the assessment of COPD patients, it has not been fully evaluated exclusively in IPF. This study was designed to evaluate the validity of the CAT in IPF. Methods: The clinical data for 106 consecutive subjects with newly diagnosed IPF who completed pulmonary function tests, partial pressure of oxygen in arterial blood (PaO2 ) at rest, 6‐min walk test (6MWT), CAT, St George's Respiratory Questionnaire (SGRQ), modified Medical Research Council (mMRC) dyspnoea grade and Hospital Anxiety and Depression Scale (HADS), were analysed. We assessed the validity of the CAT in comparison with the SGRQ. Results: The present subjects showed mild to moderate restrictive impairment on spirometry. Mean CAT score and total SGRQ were 12.8 ± 8.0 and 30.8 ± 17.7, respectively. The concurrent validity of the CAT score in comparison with the SGRQ total score was significant (r = 0.72, P  < 0.001). Internal consistency (Cronbach's α = 0.869) and repeatability over 3 months (intraclass correlation coefficient = 0.742) of the CAT were also significant. Single regression analysis showed that the CAT had significant construct validity. In multiple regression analysis, mMRC, PaO2 at rest, minimum SpO2 during 6MWT and anxiety of HADS were independent predictors for the CAT. Conclusions: The CAT is a valid health status measurement in IPF patients. Multiple regression analysis showed that the CAT was significantly correlated with dyspnoea severity, oxygenation impairment and anxiety. Abstract : The validity of the COPD Assessment Test (CAT) was evaluated exclusively in idiopathic pulmonary fibrosis (IPF) patients in comparison with the St George's Respiratory Questionnaire (SGRQ). The CAT had a significant correlation with SGRQ and was independently predicted by dyspnoea severity, oxygenation impairment and anxiety. See article, page 628